Glycated Hemoglobin and short-term Prognosis in Patients with Acute Coronary Syndrome with Diabetes Mellitus: A Prospective Cohort Study (University Heart Journal, 2021)
Background: Data on the association between glycemic control after percutaneous coronary intervention (PCI) and clinical outcomes are limited and controversial in diabetic patients. Objective:The aim of the study was to assess the impact of good glycaemic control on three months clinical outcomes in diabetic acute coronary syndrome (ACS) patients undergoing PCI, from a Bangladesh health service perspective. Materials and methods:This prospective cohort study which was conducted in UCC, BSMMU included 346 consecutive diabetic ACS patients who underwent PCI at department of cardiology, BSMMU. Diabetic patients were categorized into two groups based on their 3 months HbA1c levels: 169 (48.84%) diabetics with good glycaemic control (HbA1c < 7%) and 177 (51.16%) diabetics with poor glycaemic control (HbA1c ≥7%).The outcome was major adverse cardiovascular events (MACEs), defined as cardiac death, myocardial infarction (MI), definite stent thrombosis, target vessel revascularization and stroke. Results: At 3 months follow up, patients with poor glycaemic control had a significantly higher incidence of MI (6.2% vs 1.2%; p=0.021). No other adverse events were found significantly different between the groups at 3 months of PCI. Conclusion:Good glycaemic control to obtain HbA1c level